IMPROVING THE STABILITY OF BETANIN IN BEETROOT (BETA VULGARIS, LINN) EXTRACT USING CHITOSAN MICROPARTICLE - SUKMAWATI, ANITA; MARTHADILLA, CLARA CENDERA; RISDIYANTI, ISNA VIRA (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of this research is to investigate the ability of chitosan microparticle for maintaining stability of betanin in beetroot (Beta vulgaris, Linn) extract. Furthermore, the effect of chitosan concentration during manufacturing of microparticle also explored toward physical stability of active substance in the microparticle. Methods: Chitosan microparticles were created utilizing the ionic gelation process by employing various concentrations of chitosan (0.5, 1 and 2% w/v) and incorporating beetroot extract as the active ingredients. Physical characterization was done including Scanning Electron Microscope (SEM) imaging of microparticles, Drug Loading (DL), and Encapsulation Efficiency (EE). Microparticle stability was evaluated every week on the betanin level and colour (at 40 °C for 28 d). Results: The outcome shown that the physical properties and EE of beetroot extract in microparticles were significantly impacted by the chitosan concentration during microparticle preparation. The highest EE was found in the microparticle prepared from chitosan 1% (92.1 %). The reducing of betanin level and colour-changed can during storage for 28 d can be diminished by the chitosan microparticles. Conclusion: The chitosan microparticle has the capacity to prevent betanin from degrading. However, the chitosan concentration during the manufacture of the microparticles had a significant impact on the physical characteristics, loading capacity and ability to inhibit the degradation of the betanin as the active ingredient. The best protection was found in the microparticle prepared from chitosan 1%.